Agent-Based Modeling and Simulation in the Social Sciences (2013)
This entry reviews agent-based modeling (ABM) with respect to three aspects: (1) its main features and relationship to other simulation techniques, (2) the distinctiveness of the ABM methodology in terms of its approach to the problems of agency and explanation, and (3) open questions for practitioners in the field. The entry ends with a list of useful resources available on the web.